2020
DOI: 10.1111/apt.15677
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal and proximal gastric adenocarcinomas are rare after detection of Helicobacter pylori infection

Abstract: Summary Background Helicobacter pylori infection is the most important risk factor for non‐proximal gastric adenocarcinoma, yet some posit it is protective against oesophageal adenocarcinoma and proximal gastric cancers. Aims To evaluate the incidence of and risk factors for future oesophageal and proximal gastric cancers, utilizing the largest North American cohort of patients with previously identified H pylori. Also to identify whether treatment and eradication of H pylori alter future oesophageal and proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…H. pylori infection increases the risk of non‐cardia GC unequivocally, whereas its protective role against esophageal adenocarcinoma and proximal GC is debatable. In a retrospective study, Kumar et al aimed to identify, in the aforementioned Veterans Health Administration cohort of patients with previously diagnosed H. pylori , the risk factors for future esophageal adenocarcinoma and cardia GC 3 . Compared with whites as the reference population, the risk of future esophageal adenocarcinoma or cardia GC was similar among African Americans (SHR: 0.87, 95% CI: 0.57‐1.43) and American Indians (SHR 1.31; 95% CI, 0.18‐9.60) but substantially reduced in Asians (no cases among 213 H. pylori ‐positive) or native Hawaiian origin (no cases among 295 H. pylori ‐positive).…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…H. pylori infection increases the risk of non‐cardia GC unequivocally, whereas its protective role against esophageal adenocarcinoma and proximal GC is debatable. In a retrospective study, Kumar et al aimed to identify, in the aforementioned Veterans Health Administration cohort of patients with previously diagnosed H. pylori , the risk factors for future esophageal adenocarcinoma and cardia GC 3 . Compared with whites as the reference population, the risk of future esophageal adenocarcinoma or cardia GC was similar among African Americans (SHR: 0.87, 95% CI: 0.57‐1.43) and American Indians (SHR 1.31; 95% CI, 0.18‐9.60) but substantially reduced in Asians (no cases among 213 H. pylori ‐positive) or native Hawaiian origin (no cases among 295 H. pylori ‐positive).…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…Meta-analyses on effect of eradication HPI produced, however, inconsistent results [ 229 ]: a significantly higher risk of developing de novo GERD was demonstrated in Asian studies [ 251 ], but not in Western ones [ 252 , 253 , 254 ]. In a recent retrospective large cohort study from US ( n = 36,803 patients with HPI), rates of esophageal and proximal gastric cancers 5, 10 and 15 years after treatment/eradication of HPI were low—0.15%, 0.26% and 0.34%, respectively [ 255 ]. In the interpretation of the data on the relationship between HPI and GERD the type and location of HPI-induced gastritis should be taken into account.…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…26 However, a large retrospective study of 36,803 US veterans could not confirm the association between either H pylori status or treatment status and EAC incidence. 27 Similarly, a Swedish nationwide, population-based cohort study (n ¼ 81,919) showed that H pylori status was associated inversely with BE, although a link with EAC incidence was not found. 28 Furthermore, studies investigating the association between H pylori and reflux disease confirmed an increased risk of erosive reflux esophagitis after H pylori eradication, but did not show an increase in GERD-related symptoms.…”
Section: Q11mentioning
confidence: 99%